2014
DOI: 10.1016/j.watres.2014.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Household effectiveness vs. laboratory efficacy of point-of-use chlorination

Abstract: Treatment of water at the household level offers a promising approach to combat the global burden of diarrheal diseases. In particular, chlorination of drinking water has been a widely promoted strategy due to persistence of residual chlorine after initial treatment. However, the degree to which chlorination can reduce microbial levels in a controlled setting (efficacy) or in a household setting (effectiveness) can vary as a function of chlorine characteristics, source water characteristics, and household cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 13 publications
(20 reference statements)
1
41
0
1
Order By: Relevance
“…In comparison, a study in Ecuador (Levy et al, 2014) found that 48.8e61.3% of samples collected from storage containers with chlorinated water had detectable levels of E. coli. Chlorinated water should have lower contamination levels due to its residual disinfection capacity, but there may have been higher prevalence of E. coli in the source water or higher risks of recontamination in the Ecuador study.…”
Section: Controlled Comparisonsmentioning
confidence: 90%
“…In comparison, a study in Ecuador (Levy et al, 2014) found that 48.8e61.3% of samples collected from storage containers with chlorinated water had detectable levels of E. coli. Chlorinated water should have lower contamination levels due to its residual disinfection capacity, but there may have been higher prevalence of E. coli in the source water or higher risks of recontamination in the Ecuador study.…”
Section: Controlled Comparisonsmentioning
confidence: 90%
“…Previous studies have shown that high turbidity can affect free available chlorine in drinking. 17 Therefore, to ensure that our experiments were representative of the drinking water source used by the majority of households in Dhaka city, we prepared chlorine stock solutions using Dhaka Water Supply and Sewerage Authority (DWASA) water. The DWASA water used for laboratory experiments had a turbidity of < 1 NTU, a pH of 7.2, and free available chlorine concentration below the detection limit (< 0.01 mg/L).…”
Section: Methodsmentioning
confidence: 99%
“…14,16 However, previous studies have also found that the effectiveness of chlorine in reducing microbial contamination can vary based on source-water turbidity, source-water baseline contamination levels, and in-home contamination. 16,17 In rural Ecuador, only 17% of households with high source-water turbidity (> 10 NTU) were able to achieve the World Health Organization guideline for safe drinking water after chlorine treatment with a sodium hypochlorite (NaOCl) solution of 1.875 mg/L. 17 In alignment with this finding, a study which analyzed water samples collected from 13 African countries recommended a dosage of 1.875 mg/L NaOCl for water sources with an NTU less than 10, and 3.75 mg/L for water sources between 10 and 100 NTU to meet a free available chlorine concentration greater than 0.2 mg/L after 24 hours of storage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the same households were provided PUR, it was noted that 33% had Escherichia coli concentrations < 1 CFU/100 ml, and when provided filters, 39% had Escherichia coli < 1 CFU/100 ml (Albert, Luoto, & Levine, 2010).In this study, the performance of both aqua safe tablets and application WaterGuard tablets in removing total coliforms from KMS1sample was slightly lower compared to other samples, probably because of much higher turbidity observed. The physical-chemical properties of source water have been observed to limit bacterial reduction application of aqua safe tablets (Levy et al, 2014;Mohamed et al, 2015). Turbidity is known to negatively affect water disinfection by chlorine (Mohamed et al, 2015) by exerting chlorine demand.…”
Section: Discussionmentioning
confidence: 99%